Synthesis of seven-membered lactones by regioselective and stereoselective iodolactonization of electron-deficient olefins. Issue 49 (15th May 2020) - Tang, Pan-Ting; Shao, You-Xiang; Wang, Liang-Neng; Wei, Yi; Li, Ming; Zhang, Ni-Juan; Luo, Xiao-Peng; Ke, Zhuofeng; Liu, Yue-Jin; Zeng, Ming-Hua
Abstract : A regio- and stereoselective iodolactonization of electron-deficient olefinic acids has been reported, which provides a straightforward access to seven-membered lactones with two consecutive chiral centers. Abstract : A regio- and stereoselective iodolactonization of internal electron-deficient olefinic acids has been reported, which provides a straightforward access to a series of multi-functionalized seven-membered lactones containing two consecutive chiral centers. The ester substituents on the olefins played a key role in achieving high regioselectivity. This result was proved through experiments and DFT calculations.